Anaesthesia, surgery, obstetrics, and emergency care in Guyana - H.J. Vansell; J.J. Schlesinger; A. Harvey; J.P. Rohde; S. Persaud; K.A. McQueen (Springer, 2019)
The surgical and anaesthesia needs of low-income countries are mostly unknown due to the lack of data on surgical infrastructure and human resources. The goal of this study is to assess the surgical and anaesthesia capacity in Guyana. A survey tool adapted from the WHO Tool for Situational Analysis to Assess Emergency and Essential Surgical Care was used to survey nine regional and district hospitals within the Ministry of Health system in Guyana. In nine hospitals across Guyana, there were an average of 0.7 obstetricians/gynaecologists, 3.5 non-OB surgeons, and 1 anaesthesiologist per hospital. District and regional hospitals performed an annual total of 1520 and 10,340 surgical cases, respectively. All but 2 district hospitals reported the ability to perform surgery. An average hospital has two operating rooms; 6 out of 9 hospitals reported routine medication shortages, and 4 out of 9 hospitals reported routine water or electricity shortages. Amongst the three regional hospitals, 16.1% of pregnancies resulted in Caesarean section. Surgical capacity varies by hospital type, with district hospitals having the least surgical capacity and surgical volume. District level hospitals routinely do not perform surgery due to lack of basic infrastructure and human resources.